1879 N.C. Sess. Laws 54-55, ch. 46, §§ 1-4 - (:unkn) unknown (General Publisher, 1879)
That it shall not be lawful for any person in the hunting of wild fowl in Carteret county to use any gun other than can be fired from the shoulder.
--
Keywords: HUNTING REGULATION